The current role of imaging in the prenatal diagnosis of fetal achon-droplasia medical management and dental implications - Ion, George; Albu, Cristina-Crenguta; Albu, Dinu-Florin (International Journal of Medical Research and Review, 2017)
We present the case of a patient with the following diagnosis: 29 weeks pregnancy in evolution, fetal achondroplasia with orofacial manifestations: macrocephaly, domed forehead, depressed nasal bridge, maxillary hypoplasia and general manifestations: short fingers, swelling of the back of the hand, increased angle between the femoral head and the femoral shaft, dorsal swelling of the foot, micromelia. The diagnosis was established prenatally after an ultrasound complex investigation and confirmed postnatally. We emphasize the increasingly important current role of the prenatal ultrasound investigation in early diagnosis of congenital anomalies like fetal achondroplasia and in the correct multidisciplinary management of cases.